2016
DOI: 10.1111/bjd.14481
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger protein A20 is involved in the antipsoriatic effect of calcipotriol

Abstract: Calcipotriol exhibits its antipsoriatic function through suppressing A20 expression and stabilizing negative regulators of the NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…6 In this issue of the BJD, Liu et al found that the ubiquitinediting enzyme A20 and NF-jB p65 were strongly expressed in lesional psoriatic skin compared with nonlesional skin. 7 The authors observe that treatment with calcipotriol decreased A20 and NF-jB p65 in lesional psoriatic skin, consistent with the decrease of A20 in the skin of calcipotriol-treated K14-vascular endothelial growth factor (VEGF) mice, a murine psoriasis-like model. To further elucidate the role of A20 in psoriasis, the authors stimulated keratinocytes with a cocktail of pro-inflammatory cytokines and observed that calcipotriol increased A20 expression within 24 h and subsequently decreased the A20 expression as well as NF-jB p65.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…6 In this issue of the BJD, Liu et al found that the ubiquitinediting enzyme A20 and NF-jB p65 were strongly expressed in lesional psoriatic skin compared with nonlesional skin. 7 The authors observe that treatment with calcipotriol decreased A20 and NF-jB p65 in lesional psoriatic skin, consistent with the decrease of A20 in the skin of calcipotriol-treated K14-vascular endothelial growth factor (VEGF) mice, a murine psoriasis-like model. To further elucidate the role of A20 in psoriasis, the authors stimulated keratinocytes with a cocktail of pro-inflammatory cytokines and observed that calcipotriol increased A20 expression within 24 h and subsequently decreased the A20 expression as well as NF-jB p65.…”
mentioning
confidence: 57%
“…In this issue of the BJD , Liu et al . found that the ubiquitin‐editing enzyme A20 and NF‐κB p65 were strongly expressed in lesional psoriatic skin compared with nonlesional skin . The authors observe that treatment with calcipotriol decreased A20 and NF‐κB p65 in lesional psoriatic skin, consistent with the decrease of A20 in the skin of calcipotriol‐treated K14‐vascular endothelial growth factor (VEGF) mice, a murine psoriasis‐like model.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The role of A20 in inflammatory conditions has been well documented. An important anti‐inflammatory role for this ubiquitin has been reported in arthritis, auto‐immune diseases, cardiovascular diseases, cystic fibrosis, chronic obstructive pulmonary disease (COPD), allergies and asthma . In addition, the modulation of the expression of A20 has been demonstrated to be an important mechanism of action of certain drugs including methotrexate, quercetin and the combination of long‐acting β 2 ‐adrenoceptor agonistsand glucocorticoids .…”
Section: Discussionmentioning
confidence: 99%